Pré-operação de centros de controle de transmissão e geração de energia elétrica: procedimento para validação de manobras de equipamentosda rede elétrica - Alexandre Pinto da Silva (2011)
The Pre Operation activity prepared by Power System Control Centers has a particular meaning due to its responsibility to prepare the sequential procedures for actions in system equipment. It also upgrades the conditions for equipment shutdown and restart, helped by operating instructions, which are based on electrical and energetic studies. These scripts are done to indicate the executor, a dispatcher in the case of Operation Centers, the procedures for equipment maneuvering actions. This development is of great responsibility and complexity. It requires the concern of no errors incidence in each procedure for action sequence, which can cause serious damage to lives, equipment and environment. Despite the importance and risks involved in a sequential action procedure, this subject is not studied as it should. This fact results mainly due to its great complexity. For this reason it is important to develop strategies to validate the sequential procedures, bringing more security to the pre-operation area, during its preparation, and giving to the real time team a product already tested and ready for execution. The specific object of this work is to propose an innovative proceeding to be adopted by the pre-operation area, to validate the sequential action procedure, in order to guarantee real time safe actions. The strategy is applied to an operation center of a Brazilian power utility.